Utility of Panoramic Radiographs in the Screening of Individuals with Edentulous Arches: A Need-Analysis Study - Hrishikesh Sathyamoorthy; Navya Kuchibhotla; Mathangi Kumar; Komal Smriti; Kalyana Chakravarthy Pentapati; Vinu Thomas George; Ravindranath Vineetha (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the utility of panoramic radiographs in pre-prosthetic screening of edentulous arches. Material and Methods: Panoramic radiographs taken for three years were retrospectively analyzed. Observations from the radiographs shall be categorized and classified into either of the two categories, namely: 'findings with minimal impact on denture fabrication' and 'findings which affect denture fabrication and require further evaluation.' Anatomic variations, jaw pathologies, and residual ridge resorption patterns were assessed. Results: This study included the initial screening of 23,020 panoramic radiographs, out of which 505 (showing either one or both edentulous arches) were included for the study purpose. The age range of the subjects was from 21 to 94 years. 52.6% of the radiographs showed positive findings. More than half of the radiographs belonged to the males (52.5%). Hyperpneumatization of the maxillary sinus, crestal position of the mental foramen, and retained root fragments were the most common entities noted in the radiographs. Changes in the mental foramen were significantly higher in males than females (p=0.002). Conclusion: Observations from this study showed that panoramic radiographs have high utility for screening edentulous arches, and they should be used in routine clinical practice before denture fabrication.